China’s Energy Diplomacy to Coal Imports from Indonesia After Restricting Coal Import from Australia in 2019 - Gistyger Hasudungan Manullang; RIKA ISNARTI (Indonesian Journal of Energy, 2023)
Abstract. This study aims to analyze China's energy diplomacy regarding coal imports from Indonesia after restricting coal imports from Australia in 2019. After China limits coal imports from Australia in 2019, the supply of Chinese coal imports will decrease. This makes China need to increase its coal imports from other countries, one of which is Indonesia. Indonesia is one of the largest coal-exporting countries in the world. This can be used by China to meet its coal import needs. The author uses three indicators of Wang & Xu's energy diplomacy, namely dialogue between countries related to energy, government involvement in energy partnerships, and public energy diplomacy activities. The author uses qualitative research methods and internet-based research as data collection techniques. The findings in this study are: First, the dialogue between China and Indonesia, namely the meeting on 10 April 2019, the cooperation agreement on 24 May 2019 and 25 November 2020. Second, the Chinese government was involved in carrying out a cooperation agreement with Indonesia. Third, two Chinese non-state actors, namely CNCA and CCTDA.